The Determinants of Protection in Developing Countries: An Extended Interest-Group Approach - Torsten Amelung (Kyklos, 1989)
The article reveals empirical analysis for the political economy of trade protection in developing countries and emerging economies. Accordingly, industries that are supported by assertive interest groups and are very well organized are likely to be granted a higher degree of protection from imports than others. This paper applies an extended interests-group approach trying to establish a relationship between the organizational capabilities of the interest groups and the outcome in terms of import protection. Using data from Brazil the the model was tested in a cross-sector regression analysis.
Keywords: B27; D72; 330; Import restrictions; Political economy of trade; Organizational capability of interest groups